In vitro antioxidant activity and in vivo antigastric ulcer activity of tepal and skin extracts of Musa Paradisiaca in mice - Bashir Ado Ahmad
The current uses of ulcer drugs is limited to its side effects and potentiality of relapse. This study is aimed to explore the antioxidant activity of banana tepal methanol (TPM), ethanol (TE), aqueous (TA), skin (SKM) and flesh methanol (FM) extracts and ascertain the antiulcer potentials of the TPM and SKM. The banana parts were processed and extracted by simple maceration. Some phytochemicals were screened. Antioxidant activity was assessed using 2,2-diphenyl1-1-picryl hydrazine (DPHH) and nitric oxide (NO) radicals scavenging activities. Total phenolic content (TPC) was measured. Twenty-five albino mice were fasted for 24 hours and then randomly grouped into fie, comprising five mice each. The control group received distilled water, TPM, SKM and cimetidine (CIM) groups were pretreated with 100mg/kg tepal, skin and cimetidine for seven days respectively. On day seven, a single dose of indomethacin (48mg/kg) was administered, in this case including the induced group (IND+PYL). All the animals were fasted overnight. On the 8th day, the pylorus was ligated. The animals were sacrificed, and the removed stomachs were prepared of the evaluation pf ulcer index and gastric wall mucus. pH and volume were measured from the gastric juice. The results revealed some phytochemicals like phenols, flavonoids ect., in the extracts. TPM had the highest DPPH radical scavenging activity (IC..50=22.5 µg/mL) while FM showed the least (no IC..50). Maximum NO inhibition was seen in TA (41.05%) and still FM showed the least (22.34%). TPM had the highest TPC (8000 µg GAE/g extract) than all other extracts. TPM and SKM prevented the induced ulcer by 68.80±14.82% respectively. Significant rise (p<0.05) in gastric juice pH (3.79±0.24) was noticed in TPM group. However, the decrease in gastric juice volume and increased gastric wall mucus by TPM and SKM were not statistically significant (P>0.05). The results showed that TPM and SKM were able to prevent IND+PYL induced ulcer; possibly by strengthening the gastric mucosa, decreasing the gastric juice acidity and antioxidative mechanism. Further investigations are needed to validate the use of these parts for ulcer treatment.